Darwin's cathedral : evolution, religion, and the nature of society - Wilson, David Sloan (The University of Chicago Press, 2002)
"From Calvinism in sixteenth-century Geneva to Balinese water temples, from hunter-gatherer societies to urban America, Wilson demonstrates how religions have enabled people to achieve by collective action what they never could do alone. He also includes a chapter considering forgiveness from an evolutionary perspective and concludes by discussing how all social organizations, including science, could benefit by incorporating elements of religion. Religious believers often compare their communities to single organisms and even to insect colonies. Astoundingly, Wilson shows that they might be literally correct. Intended for any reader, Darwin's Cathedral will change forever the way we view the relations among evolution, religion, and human society."--Jacket